Factors Influencing Budgeting: Case Study In Village Goverment - Ana Sopanah; Harnovinsah Harnovinsah; Rafrini Amyulianthy (Innovation Business Management and Accounting Journal, 2023)
The village budget is a village development appraisal plan carried out independently. Meanwhile, each village has its own culture, rules, and uniqueness. So it becomes a problem that must be coordinated between village components. Therefore, it is necessary to know what factors influence village budgets, especially unique villages, Sumber Porong Village, Indonesia. This study aims to explain the influence of community participation factors, leadership styles, politics and budget transparency on village budgeting. The research method uses explanatory research with a quantitative approach. They are using a purposive sampling method in determining the sample, while the number of samples is 20 respondents. The characteristics of the sample are those who have participated in and supervised budgeting in Sumber Porong Village. Using SEM Partial Least Square (PLS). The study results show that budget transparency affects budgeting, as indicated by meeting the needs of the village community. The leadership style in encouraging the achievement of village development greatly affects budget transparency. In addition, leadership style and politics have a positive effect on budgeting.